(untitled) (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: The aim of this retrospective analysis was to evaluate the safety and efficacy of local hyperthermia (HT) and reirradiation (ReRT) in the management of preirradiated locoregional recurrent breast cancers at Kantonsspital Aarau, Switzerland. METHODS: Twenty-four previously irradiated patients who had developed locoregional recurrences in the chest wall or breast, with or without regional lymph node involvement, were reirradiated to a mean dose of 36.8 Gy (range 20–50 Gy) delivered at a mean dose per fraction of 2.33 Gy (range 1.8–4.0 Gy). All patients received local HT at 41 to 43 °C, once or twice a week prior to radiotherapy. Online thermometry was carried out during the hyperthermia sessions. RESULTS: An overall objective response rate of 91.7% (22/24) with a complete response in 66.7% (16/24) of patients and partial response in 25% (6/24) of patients was observed. Post-thermoradiotherapy follow-up ranged from 1 to 38 months (median 10 months). The 3-year actuarial local control rate was 59.7%. More patients who attained complete response had sustained locoregional control until their death or last follow-up when compared with those who were partial or non-responders (median local disease-free survival for complete responders not reached; for partial and non-responders 4 months; p <0.001). Post-retreatment median overall survival for all 24 patients was 10 months. Grade III/IV acute toxicity was seen in only one patient and no patient had any significant late morbidity. CONCLUSIONS: ReRT and HT is an effective and a safe modality to treat locoregional recurrences in previously irradiated breast cancers. The approach can lead to sustainable long-term palliation with minimal morbidity.